1997
DOI: 10.1021/jf960366o
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Character Impact Odorants in Fresh Strawberry Juice by Quantitative Measurements and Sensory Studies on Model Mixtures

Abstract: Twelve odorants, previously identified with high flavor dilution (FD) factors, were quantified in a fresh strawberry juice by using stable isotope dilution assays. Calculation of odor activity values (ratio of concentration to odor threshold), on the basis of odor thresholds in water, revealed especially the six compounds (Z)-3-hexenal (green), 4-hydroxy-2,5-dimethyl-3(2H)-furanone (caramel-like, sweet), methyl butanoate (fruity), ethyl butanoate (fruity), methyl 2-methylpropanoate (fruity), and 2,3-butanedion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
273
0
13

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(290 citation statements)
references
References 10 publications
4
273
0
13
Order By: Relevance
“…Because volatiles differ in their organoleptic properties, relatively few of these are likely to contribute significantly to flavor. By application of the aroma value concept (i.e., the ratio of concentration to odor threshold), it was shown that only ;15 odor-active compounds make an important contribution to strawberry flavor (Schieberle and Hofmann, 1997). Studies have demonstrated that strawberry aroma is the result of the combined perception of fruity (ethyl butanoate, ethyl hexanoate, and methyl 2-methylbutanoat), green (Z-3-hexenal), sweaty (butanoic acid and 2-methylbutanoic acid), peach-like (g-decalactone), and caramel-like [4-hydroxy-2,5-dimethyl-3(2H)-furanone (HDMF; Furaneol) and 2,5-dimethyl-4-methoxy-3(2H)-furanone (DMMF)] flavor notes (Pyysalo et al, 1979;.…”
Section: Introductionmentioning
confidence: 99%
“…Because volatiles differ in their organoleptic properties, relatively few of these are likely to contribute significantly to flavor. By application of the aroma value concept (i.e., the ratio of concentration to odor threshold), it was shown that only ;15 odor-active compounds make an important contribution to strawberry flavor (Schieberle and Hofmann, 1997). Studies have demonstrated that strawberry aroma is the result of the combined perception of fruity (ethyl butanoate, ethyl hexanoate, and methyl 2-methylbutanoat), green (Z-3-hexenal), sweaty (butanoic acid and 2-methylbutanoic acid), peach-like (g-decalactone), and caramel-like [4-hydroxy-2,5-dimethyl-3(2H)-furanone (HDMF; Furaneol) and 2,5-dimethyl-4-methoxy-3(2H)-furanone (DMMF)] flavor notes (Pyysalo et al, 1979;.…”
Section: Introductionmentioning
confidence: 99%
“…No work has been undertaken until now on key flavour compounds such as ethyl-3-methyl butyrate and furaneol in strawberry aroma [23], or isopropyl-methoxypyrazines and vanillin in chocolate [24]. Therefore, these flavour-producing compounds were analyzed in the present study, together with related molecules in order to assess the influence of structural differences of substances on the binding to BLG.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, more than 360 volatiles have been identified (Latrasse, 1991;Nijssen, 1996;Zabetakis and Holden, 1997), but only 15 to 20 of them in wild varieties of strawberry are believed to be essential for sensory quality, together with nonvolatile sugars and organic acids (Schieberle and Hofmann, 1997). In contrast, in cultivated varieties of strawberry, only about six odor-active compounds have been identified as contributors to fruit flavor (Raab et al, 2006;Ulrich et al, 2007).…”
mentioning
confidence: 99%